Reproductive justice: an introduction - Ross, Loretta J. (Reproductive justice: a new vision for the twenty-first century, 2017)
"Reproductive Justice is a first-of-its-kind primer providing a comprehensive yet succinct description of the field. Written by two legendary scholar-activists, Reproductive Justice introduces students to an intersectional analysis of race, class, and gender politics. Clearly showing how reproductive justice is a political movement of reproductive rights and social justice, the authors illuminate how, for example, a low-income, physically -disabled woman, living in West Texas with no viable public transportation, no healthcare clinic, and no living-wage employment opportunities, faces a complex web of structural obstacles as she contemplates her sexual and reproductive intentions. Putting the lives and lived experience of women of color at the center of the book, and using a human rights analysis, the authors show how reproductive justice is significantly different from the pro-choice/anti-abortion debates that have long-dominated the headlines and mainstream political conflict. In a period in which women's reproductive lives are imperiled, Reproductive Justice provides an essential guide to understanding and mobilizing around women's rights in the 21st century. Reproductive Justice: A New Vision for the 21st Century Series publishes works that explore the contours and content of reproductive justice. The series will include primers intended for students and those new to reproductive justice as well as books of original research to continue to further knowledge and impact society."--Provided by publisher